Depression and Associated Factors Among Diabetic Patients Undergoing Diabetic Retinopathy Assessments at a Tertiary Care Center: A Cross-Sectional Study - Upaphong P; Choovuthayakorn J; Choovuthayakorn J; Phinyo P; Patikulsila D; Nanegrungsunk O; Chaikitmongkol V; Kunavisarut P; Apivatthakakul A; Wongpakaran N; Wongpakaran T (Clinical Ophthalmology)
Phit Upaphong,1 Janejit Choovuthayakorn,1 Jirachaya Choovuthayakorn,1 Phichayut Phinyo,2,3 Direk Patikulsila,1 Onnisa Nanegrungsunk,1 Voraporn Chaikitmongkol,1 Paradee Kunavisarut,1 Atitaya Apivatthakakul,1 Nahathai Wongpakaran,4 Tinakon Wongpakaran4 1Department of Ophthalmology, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 2Clinical Epidemiology and Clinical Statistics Center, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 3Department of Biomedical Informatics and Clinical Epidemiology (Bioce), Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 4Department of Psychiatry, Faculty of Medicine, Chiang Mai University, Chiang Mai, ThailandCorrespondence: Janejit Choovuthayakorn, Department of Ophthalmology, Faculty of Medicine, 110 Intavaroros Road, Muang, Chiang Mai, 50200, Thailand, Email janejit.c@cmu.ac.thPurpose: To explore the prevalence of depression and its associated factors among diabetic patients attending the retina unit at Chiang Mai University Hospital for diabetic retinopathy (DR) or diabetic macular edema (DME) screening and/or treatment.Patients and Methods: This cross-sectional study recruited consecutive diabetic patients scheduled for ophthalmic evaluations between July 1, 2022, and January 31, 2023. Participants completed in-person interviews to provide demographic information, medical history, and mental health status. Depression severity was assessed using the Outcome Inventory-21, while vision-related quality of life (VRQoL) was measured with the National Eye Institute Visual Functioning Questionnaire-25 (NEI VFQ-25). Ocular characteristics were extracted from medical records. The primary outcomes included the prevalence of depression and its association with VRQoL, anxiety, visual acuity, and DR/DME severity.Results: A total of 304 diabetic patients participated, with 55.6% (n = 169) being male. The mean (standard deviation, SD) age was 56.3 (11.4) years, and the mean (SD) visual acuity (VA) in the better-seeing eye was 0.4 (0.3) LogMAR. Bilateral proliferative DR and bilateral center-involved DME were observed in 50.6% and 18.4% of participants, respectively. The mean (SD) composite score for the NEI VFQ-25 was 79.3 (18.1), with the color vision subscale showing the highest score at 93.3 (18.3). Depression was identified in 11 patients (3.6%, 95% confidence interval: 2.0 to 6.4%). Multivariable linear regression revealed that lower VRQoL and higher anxiety levels were significantly associated with depressive symptoms, while no significant correlation was found with VA or DR/DME severity.Conclusion: VRQoL and anxiety levels are key factors associated with depression in diabetic patients with DR/DME, with VRQoL exhibiting a stronger association than VA. Incorporating patient-reported outcome measures into clinical care may enhance mental health assessment and overall healthcare quality, enabling earlier detection of depression risk among diabetic patients and supporting timely intervention.Plain Language Summary: Diabetic eye diseases like DR and DME can affect vision and make daily life more difficult, but their impact is not just physical—it can affect mental health too. This study showed that people who felt their vision problems were interfering with daily life and had higher anxiety were more likely to be depressed, no matter how severe their actual eye condition was. This shows why we need to focus on mental health as part of diabetic eye care. Regular screening for depression and anxiety could help improve both well-being and treatment outcomes.Keywords: depressive symptoms, mental distress, psychological burden, quality of life, retinal disease, visual-related function